Let's solve the equation step by step:
Given: \[ 6(2x + 4) - 24 = 12x \]
-
Distribute the 6 on the left side: \[ 6 \cdot 2x + 6 \cdot 4 - 24 = 12x \] \[ 12x + 24 - 24 = 12x \]
-
Simplify the left side: \[ 12x + 0 = 12x \] \[ 12x = 12x \]
This tells us that the left side and right side are equal for all values of \( x \). This is a true statement regardless of the value of \( x \).
Therefore, the equation has infinite solutions.
Conclusion: The correct response is: The equation has infinite solutions.